PERANAN ACTIVITY-BASED COSTING SYSTEM DALAM MENGANALISIS LABA PER PELANGGAN UNTUK MENINGKATKAN LABA DEPARTEMEN PRINTING PT TJ. - Arthur Purboyo; Aileen Kurniawan (Bina Ekonomi, 2007)
Many managers  think  that increases  in sales will automatically increase  company's  profit. With this assumption,  the company will accept order  from customer without making  judgment  on the capacity of company  consumed  by that order. The background  of this thinking is catted volume-related. But,  in many  cases, cost depends  on the activity consumed  to accomplish an order. So, cost allocated based on unit of output sometimes  will cause overcosted or undercosted. On of the solution  to over or undercosted  is cost allocation based on activity consumed by the product or the order. This cost allocation  is called activity-based  costing. Activity-based  costing  systems help will provide complete and accurate  information  that are needed by the management to make better decision based  on cost of an order.Keywords:  overcosted,  undercosted,  activity-based costing, activity based management